Effect of annealing temperature on the Structural, Morphological and Optical properties of PbS Films deposited using spray pyrolysis Technique - J.A.Makko; M. L. Madugu; A.I. Nafad; M.U Kael; M.D. Muhammad (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Lead sulphide (PbS) semiconductor material has attracted a great deal of attention because of its applications in optoelectronics, solar control coatings, gas and humidity sensor and photo electrochemical solar cells. PbS polycrystalline thin films prepared by the spray pyrolysis technique was deposited onto glass substrates at a substrate temperature of 300oC and was annealed at 300◦C and 400◦C. The solution containing Pb precursors was used to obtain good quality film deposits at optimized parameters. The characterization of these films was performed using X-ray diffraction (XRD), Scanning electron microscopy (SEM) and Ultraviolet-visible spectrophotometer (UV-VIS) to explore the structural, morphological and optical properties of the PbS films respectively. The prepared films are crystalline in nature and well adhered to the substrates. The films are polycrystalline with preferred orientation along the 200 cubic phase. The optical properties were determined from ultraviolet-visible spectroscopy measurements in the absorbance energy range 200–800 nm. The UV-visible analysis shows the band gap value of the annealed PbS thin films as 3.6 eV which makes it suitable for window layer in photovoltaic devices. The micrographs revealed that PbS thin films are polycrystalline and uniformly distributed.